The globalization of energy : China and the European Union - Amineh, Mehdi Parvizi; Guang, Yang (International comparative social studies, 2010)
Since the conclusion of the 1985 trade and cooperation agreement between the European Community and China, a new political dynamic has been set in motion between two emerging entities: industrializing China and integrating Europe. It is reflected in, among others, European Commission policy strategy papers and, probably more importantly, in numerous sectoral dialogues and agreements. Europe has become China's largest export destination. For the E.U., China has become its second largest trading partner and its most important source of imports.